Greener Catalysis for Environmental Applications - Wacławek, Stanisław (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is devoted to "greener catalysis for environmental applications", and primarily covers the catalytic synthesis of value-added chemicals, as well as the catalytic removal of pollutants. The most important topics covered were the conversion of waste to the product, solvent-free conditions as well as toxicity assessment of the reaction products.